A CALPHAD-based model on the viscosities: A case study on Zr–Fe–Cu liquid alloys. (December 2022) - Li, Xi; Li, Juntao; Wu, Liang; Zhang, Fan; Chen, Jinwei; Huang, Jiajia; Zhang, Wei-Bing; Du, Yong
Abstract: Viscosity is an important thermodynamic property for alloy design, especially for refractory alloy. CALculation of PHAse Diagram (CALPHAD)-based viscosity calculations are highly desirable since they can accurately predict the viscosity in the alloy with different compositions. However, the current viscosity calculation model lacks the ability to fit the situations where the viscosity varies largely with temperature. Here, we propose a new equation to describe the excess viscosity using an exponential equation. The physical meaning of each parameter is explained. Moreover, the proposed model is not only compatible with the previous model but also suitable for all the situations. We further calculate the viscosity using different models in the Zr–Fe–Cu system which is important in the fields of nuclear fuel and magnetic refrigerants. The proposed model gives a better description than the other two models with fewer optimizing parameters, verifying the advantages of the current model. Based on the established viscosity database of Zr–Fe–Cu, we further predict its metallic glass-forming ability. The theoretical analyses together with the viscosity calculation examples suggest that the proposed model can provide accurate viscosity calculations in liquid alloys as a function of temperature and composition. Therefore, the proposed model is suitable for the design of refractory alloys.